2018
DOI: 10.1016/j.compfluid.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order compact scheme for high-performance computing of stratified rotating flows

Abstract: To take advantage of modern generation computing hardware, a scalable numerical method, based on higher-order compact scheme, is described to solve rotating stratified flows in cylindrical annular domains. An original approach combining 2d-pencil decomposition and reduced Parallel Diagonal Dominant is proposed to improve the parallelization performance during the computation of Poisson/Helmholtz solvers and time explicit terms. The developed technique is validated with respect to analytical solutions, using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…To overcome these difficulties, a direct numerical simulation (DNS) solver combining fourth-order accuracy space discretization and high-performance computing (HPC) has been developed by Abide et al [19] to investigate the SRI dynamics. The code solves the Navier–Stokes equations using the Boussinesq approximation to account for the buoyancy forces.…”
Section: Parameter Studymentioning
confidence: 99%
“…To overcome these difficulties, a direct numerical simulation (DNS) solver combining fourth-order accuracy space discretization and high-performance computing (HPC) has been developed by Abide et al [19] to investigate the SRI dynamics. The code solves the Navier–Stokes equations using the Boussinesq approximation to account for the buoyancy forces.…”
Section: Parameter Studymentioning
confidence: 99%
“…More recently, numerical results and comparisons with experimental data have been performed also for the large BTU experiment [22,23,43]. To take advantage of modern generation computing hardware, a scalable numerical method, based on a higher-order compact scheme, has been developed to solve rotating stratified flows in cylindrical annular domains [44]. This code was successfully applied to study stratorotational instability [45] but also to simulate baroclinic instability using the geometry and the parameters of the large BTU tank.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…The problem is that matrix transpose becomes a global all-to-all operation when data is distributed on multiple GPUs. Many studies such as [1], [2], [7] have used global transpose in simulations of wallbounded flows. They have obtained a weakly linear scaling on thousands of CPU cores, but reported that global transpose takes up a majority of the total computation time.…”
Section: Introductionmentioning
confidence: 99%